Challenges to, and prospects for, reverse engineering the gastrointestinal tract using organoids. Issue 8 (August 2022) - Kakni, Panagiota; Truckenmüller, Roman; Habibović, Pamela; Giselbrecht, Stefan
Abstract : For over a decade, organoids mimicking the development, physiology, and disease of the digestive system have been a topic of broad interest and intense study. Establishing organoid models that recapitulate all distinct regions of the gastrointestinal tract (GIT) has proven challenging since each tissue surrogate requires tailor-made modifications of the original protocol to generate intestinal organoids. In this review, we discuss the challenges and current advances of the GIT organoid models. Moreover, we envision the next-generation GIT organoids as integrated organoid models, able to recapitulate structural and functional characteristics of multiple regions of the digestive tube in a single in vitro model. We discuss these new trends and provide an outlook for the future of GIT in vitro models. Highlights: Organoids are self-organizing 3D cell culture systems that constitute a unique tool for studying development and disease. Over the past decade, efficient protocols to grow organoids that resemble the different parts of the GIT have been established. Bioengineering approaches have been used to improve organoid cultures. Organoid fusion and on-chip methods are explored to increase complexity of organoids to better recapitulate in vivo tissues.